(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, the growth of lending in the country is mainly due to the financing of investment projects of state programs for the development of the sector and territories, lending to small businesses and private entrepreneurship, and supporting the people who start their business.First of all, we need to create an effective system of credit and investments from abroad, learn how to use each loan accurately. The time has come for this issue to be seven-dimensional, once-cut, and carefully thought through. ”It is well-known that worldwide Doing Business research and valuation make a significant contribution to the development of countries, including enhancing the business and competitive environment, serving as a "reliable bridge" for investors and countries seeking them.